Engineering of Hybrid SiO2@N-P-Fe Catalysts with Double-Ligand for Efficient H2 Production from HCOOH - Anna Sotiriou; Eleni Aspri; Yiannis Deligiannakis; Maria Louloudi (Energies, 2025)
Two Fe-based hybrids, [SiO2@NP(Ph)2/FeII/PP3] and [SiO2@NP(t-Bu)2/FeII/PP3], were synthesized using the double-ligand approach by covalently grafting NP ligands onto the surface of SiO2. Both catalytic systems were evaluated for H2 production through formic acid dehydrogenation (FADH), revealing important efficiency without requiring additional additives and/or co-catalysts. During the continuous addition of FA, [SiO2@NP(Ph)2/FeII/PP3] and [SiO2@NP(t-Bu)2/FeII/PP3] demonstrated great stability, achieving total TONs = 20,636 and 20,854, respectively. FT-IR and Raman spectroscopy provided insights into the role of NP ligands, such as NP(Ph)2 and NP(t-Bu)2, on the assembly and structural configuration of active hybrid Fe catalysts and their ability to dehydrogenate formic acid. Additional studies, including in situ mapping of the solution potential (Eh) of the catalytic reaction and an Arrhenius study of the activation energy (Ea), revealed a correlation between Ea and H2 production rates: the system [SiO2@NP(Ph)2/FeII/PP3] with an Ea = 29.4 KJ/mol shows an H2 production rate of 58 mL-H2/min, while [SiO2@NP(t-Bu)2/FeII/PP3] with a Ea = 50.6 KJ/mol shows an H2 production rate of 55 mL-H2/min. This is the first example of a heterogeneous FADH system where the original strategy of a “double-ligand” has been demonstrated for homogeneous FADH catalytic systems. Herein we demonstrate that we can engineer a decrease in the activation barrier Ea via two synergistic steps: (i) via grafting of the NP ligand onto SiO2 and (ii) using PP3 as double ligand. This strategy leads to a boost in the H2 production efficiency of [SiO2@NP(Ph)2/FeII/PP3] as a heterogeneous catalyst, which for the first time has been shown to be able to outperform the parental reference/homogenous catalyst [FeII/PP3].